Synthesis of copper nanoparticles supported on MoO3 using Sun spurge leaf extract and their catalytic activity. (4th September 2018) - Janmohammadi, Mohsen; Amini, Mojtaba; Sabaghnia, Naser; Akbari, Ali; Gautam, Sanjeev; Hwa Chae, Keun
Abstract : Copper nanoparticles supported on MoO3 (Cu NPs/MoO3 ) were prepared by a green method using Sun spurge leaf extract. Cu NPs/MoO3 nanoparticles were characterized by X‐ray diffraction analysis, energy dispersive X‐ray analysis, scanning electron microscope and transmission electron microscope. The catalytic activity of this well‐defined material in three‐component CuAAC reactions was tested to produce 1, 4‐disubstituted‐1, 2, 3‐triazoles in good to excellent yields in water as a green solvent. More importantly, the catalyst can be recovered and reused efficiently up to five consecutive cycles with no significant loss of catalytic activity. Abstract : The multicomponent 1, 3‐dipolar cycloaddition of terminal alkynes, sodium azide and various organic halides in the presence of green‐synthesized copper nanoparticles supported on MoO3 was studied.